Understanding the Government's Strategy in Public Policy Making in the Era of Mutikcrisis in Indonesia: Study of Public Policy Analysis - Malik Malik; Julinta Paulina; Ade Iskandar; B.M.A.S. Anaconda Bangkara; Adi Mursalin (Budapest International Research and Critics University, 2022)
This study discusses the understanding of public policy-making by the government to respond to the pandemic, which has given rise to many difficulties among citizens because the government has issued various policies during a multi-crisis. The author understands that every policy has taken certainly impacts policies in regular times and government policies in times of crisis; of course, the impact will be different. To strengthen our discussion, we have received support from many scientific publications we have studied in the phenomenological approach, a way to get an exceptional understanding of the existing data. Our literature search was conducted electronically on several journals and book publications that discuss issues of public policy making in response to pandemics in multi-crisis times in many application contexts. Based on the results of the study and discussion, we can summarize that in public policy-making in times of multi-crisis, the government has been faced with a dilemma between the commitment to respond to the pandemic to protect the entire nation from the threat of the COVID-19 pandemic and having to accept the consequences of policies taken in a very precarious atmosphere. Hopefully, these findings will be the subject of discussion in similar studies in the future.